2011
DOI: 10.1139/b11-030
|View full text |Cite
|
Sign up to set email alerts
|

Molecular phylogeny and reticulate origins of several American polyploid Hordeum species

Abstract: The phylogeny of diploid species in the genus Hordeum has been studied intensively. Although the origin of American polyploid species has been analyzed using multiple-copy internal transcribed spacer sequences, the origins of these species in Hordeum remain unclear. The objectives of our study were to elucidate the origins of American polyploid species and to explore phylogenetic relationships of these polyploids to diploid Hordeum and other diploid species in Triticeae using a single copy of a nuclear gene, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 47 publications
1
9
1
Order By: Relevance
“…One sequences from E. confusus (PI 598463k) showed a 23 bp deletion at position 352. An 82 bp insertion was found in the sequences from polyploid species H. fuegianum , H. jubatum , and H. tetraploidum , and diploid Australopyrum velutinum and Taeniatherum caput-medusae as reported by Wang and Sun [35], and Petersen and Seberg [31], respectively. The sequence from E. trachycaulus (PI 537323L) showed a 30 bp insertion at position 1054.…”
Section: Resultssupporting
confidence: 67%
See 4 more Smart Citations
“…One sequences from E. confusus (PI 598463k) showed a 23 bp deletion at position 352. An 82 bp insertion was found in the sequences from polyploid species H. fuegianum , H. jubatum , and H. tetraploidum , and diploid Australopyrum velutinum and Taeniatherum caput-medusae as reported by Wang and Sun [35], and Petersen and Seberg [31], respectively. The sequence from E. trachycaulus (PI 537323L) showed a 30 bp insertion at position 1054.…”
Section: Resultssupporting
confidence: 67%
“…californicum might be one diploid genome donor of H. arizonicum , and the second genome donor of H. arizonicum might be the common ancestor of H. brachyantherum subsp. brachyantherum , and showed that one copy of DMC1 sequences of H. arizonicum fall outside the Hordeum clade of the tree [35]. DMC1 data here suggested if the St genome was not the donor species to one copy of genome in H. arizonicum , gene flow has occurred between H. arizonicum and some Elymus StH genome species during evolutionary process.…”
Section: Discussionmentioning
confidence: 62%
See 3 more Smart Citations